On the Heterogeneity of Leveraged Going Private Transactions - Halpern, Paul; Kieschnick, Robert; Rotenberg, Wendy (Review of Financial Studies, 1999)
[In contrast to previous literature, we argue that there are two types of poorly performing firms going private through a leveraged buyout (LBO). One group consists of firms in which managers own an insignificant fraction of their firm's stock and are vulnerable to a hostile takeover. The other group consists of firms in which managers own a significant fraction of their firm's stock and so face little risk of hostile takeover. Our evidence indicates that there are two such groups of LBOs and that their motivations and posttransaction actions are different.]